Self-conciliation settlement in customs crimes in terms of their legal organization - Hussein, Alaa; Oloum, Mohammed (Journal of Legal Sciences, 2022)
The conciliatory settlement system in customs crimes as a means of managing the criminal case amicably between the competent authority and the violator, if its conditions are met and it is legally established, the prosecutions of the violator will be stopped, and the criminal case lapses if a conciliatory settlement is concluded before the criminal lawsuit or after its filing During the consideration thereof, but if a conciliatory settlement is concluded with the violator after the issuance of a ruling in the criminal case from the competent customs court before he acquires the final degree, then he shall drop the customs fine (civil compensation), drop the fine penalty, and drop the imprisonment penalty unless the judgment is in its regard. The degree has been acquired in exchange for a certain amount agreed upon by both parties.